The Space-Age Presidency of John F. Kennedy : A Rare Photographic History - Bisney, John, 1954-; Pickering, J. L., 1957- (Book collections on Project MUSE., 2019)
"In this engaging and inspiring work, John Bisney and J.L. Pickering have written and illustrated a thorough history of John F. Kennedy's role in developing the United States' space program. Ironically, despite his close association with the race to space, Kennedy initially thought the space program was too expensive and did not support a manned space flight until the Russians sent Yuri Gagarin into orbit just a few months after Kennedy's inauguration. Now, a century after Kennedy's birth, the United States has reached the moon, sent probes into deep space, and had its astronauts spend extended time in space, all of which are a legacy of Kennedy's presidency, Surprising, though, there hasn't been a photographic history of Kennedy's involvement in the space race despite the visual glamour associated with the space race and Kennedy's presidency until this engaging book by two widely respected chroniclers of the race to space"--